Impacts of the Changjiang diluted water on sinking processes of particulate organic matters in the East China Sea. (1st December 2017) - Sukigara, Chiho; Mino, Yoshihisa; Tripathy, Sarat Chandra; Ishizaka, Joji; Matsuno, Takeshi
Abstract: Intensive surveys with repeated CTD and microstructure turbulent observations, water and sediments sampling as well as onboard incubation and sediment trap experiments were conducted to reveal the nitrogen budget in the center of the East China Sea (ECS) during July 2010 and 2011. Low salinity water (Changjiang Diluted Water, CDW) covered the study area in 2010, but not in 2011. Higher chlorophyll a (chl. a ) concentration, primary productivity, and downward particle flux in the upper layer were observed in 2010 than those in 2011. Existence of the CDW resulted in a steep pycnocline and an associated subsurface chl. a maximum (SCM) layer directly beneath the CDW. From chemical analyses of particulate carbon and nitrogen contents and isotope ratios, it became apparent that the particles sunk out the euphotic zone in 2010 was primarily originated in the CDW layer and secondly in the SCM layer. Whereas, in 2011, sinking particles were originated in the surface layer but a part of them were decomposed in the bottom of pycnocline. Our findings indicate that the CDW would supply particles into the deep layer and contribute to the downward transport of materials and the efficiency of biological pump in the ECS.